Rational design, synthesis, antiproliferative activity against MCF-7, MDA-MB-231 cells, estrogen receptors binding affinity, and computational study of indenopyrimidine-2, 5-dione analogs for the treatment of breast cancer. (15th May 2022) - Ejaz, Iqra; Javed, Muhammad Aamir; Jan, Muhammad Saeed; Ikram, Muhammad; Sadiq, Abdul; Ahmad, Sajjad; Rashid, Umer
Graphical abstract: Highlights: Synthesized indenopyrimidine-2, 5-dione core as a starting point of current research. Excellent antiproliferative activity against MCF-7 breast cancer cells. Safe against non-malignant HEK-293. Competitive binding assay was performed on estrogen receptors ERα and ERβ. CAM assay showed that compounds can cause apoptosis in human breast cancer cells. Docking studies and in-silico pharmacokinetic prediction. Abstract: Based on the structural architecture of estrogen receptors (ER) agonists/antagonists, we rationally designed and synthesized indenopyrimidine-2, 5-dione analogs as a starting point of current research targeting estrogen receptors. These analogs were evaluated for their antiproliferative activities against breast cancer MCF-7 (ER + ), MDA-MB-231 (ER - ) and non-cancerous HEK-293 cells using MTT assay. Compounds with high antiproliferative activity against MCF-7 breast cancer cells were found devoid of cytotoxicity against HEK-293 cells. Competitive binding assay of estrogen receptors ERα and ERβ showed that diethanolamine derivative of 4-trifluoromethyl phenyl derivative 30 displayed 77.5-fold strong binding affinity towards ERα (IC50 = 0.004 μM) as compared to ERβ (IC50 = 0.31 μM). The calculated RBA value of compound 30 indicated that it has greater affinity with ER than estradiol. By docking studies, we demonstrated that high binding affinity with ERα is due to binding orientation and interaction of CF3 with a number of key amino acid residues present in the active site of ERα.